Prevalence, genomic characteristics, and transmission dynamics of mcr-1-positive Salmonella enterica Typhimurium from patients with infectious diarrhea - Cong Shen; Furong Ma; Suiyan Deng; Lan-Lan Zhong; Mohamed Abd El-Ga; Guili Zhang; Bin Yan; Min Dai; Fan Yang; Yong Xia; Guo-Bao Tian (Elsevier, 2021)
Background: Previous studies reported the prevalence of mcr-1 among clinical infected Salmonella isolates in China. However, the transmission dynamics of mcr-1 in different ecological niches were not well investigated. Our objective is to exhibit the transmission dynamics of mcr-1 in Salmonella. Methods: 598 Salmonella isolates were recovered from ten hospitals; besides 936 pig faces and 167 pork samples were collected from January 2015 to December 2017 in Guangzhou, China. PCR and sequencing were used to identify mcr-1-positive Salmonella. Antimicrobial susceptibility testing was performed with 16 antimicrobials. Conjugation, S1-PFGE, and Southern blot were used to determine the transferability and location of mcr-1. Whole-genome sequencing was used to investigate pangenome, phylogeny, plasmid, and transposon. Results: Eleven mcr-1-positive Salmonella isolates were identified from patients with infectious diarrhea. Five pig fecal samples and three pork samples contained mcr-1-positive Salmonella isolates. All isolates were multi-drug resistant. The mcr-1 genes were located on ∼210−250 kb IncHI2-pST3 plasmids, and 12 mcr-1 genes were transferable. All isolates were assigned to ST34 or its genetically closed STs. The distribution of the core-genome network was significantly correlated with source distributions. The accessory genes-based network demonstrated that the diverse clonal complexes could share highly similar accessory genomes. Conclusions: The prevalence of mcr-1-positive Salmonella among different sources was low. Clonal transmission could not be the main reason for the expansion of mcr-1-positive Salmonella, but be attributed to the horizontal transfer of IncHI2-pST3 plasmid. Continuous surveillance on Salmonella should be performed to investigate the response of colistin banning in food-producing animals by mcr-1-positive Salmonella populations.